Molecular characterisation of potential vaccine candidates from Anaplasma marginale strains in South Africa - Collins, Nicola E. (University of Pretoria, 2018)
Bovine anaplasmosis, a tick-borne disease caused by the rickettsia Anaplasma marginale, has a significant economic impact for cattle farmers in South Africa. We have estimated the economic cost due to mortality arising from bovine anaplasmosis in the country to be R115 million ($US9.6 million) per year. Further costs are attributable to chemotherapeutic treatment and tick control using acaricides. Anaplasma centrale is a species that is closely related to A. marginale, and in most cases causes a milder, less virulent form of anaplasmosis. It provides cross protection against field strains of A. marginale infection and is therefore employed as a blood vaccine against bovine anaplasmosis in some countries, including South Africa. Despite the economic impact of this disease, there are few studies on the prevalence and control of bovine anaplasmosis in South Africa. This study was therefore carried out in order to evaluate the presence and genetic diversity of A. marginale in the country using quantitative real-time PCR (qPCR) and repeat variation of MSP1a, respectively. In a comprehensive examination of 517 bovine samples from all provinces of South Africa, using the A. marginale and A. centrale qPCR, A. marginale was detected in 57% of our test samples. The rickettsial pathogen was present in all provinces of South Africa with the exception of the Northern Cape province where the tick vector is absent. However, due to recently reported range extension of the important anaplasmosis tick vector Rhiphicephalus microplus, it is believed that this situation may change, and needs close monitoring. Anaplasma centrale was also detected in 17% of the samples, with 15% of the samples being co-infected. An analysis of A. marginale strains present in the samples revealed high genetic diversity, as reflected by the 190 genotypes derived from 99 Msp1a amino acid repeats. This genetic diversity is attributable to a high rate of evolution. Our data also reveal that 22% of the 99 amino acid repeats and, interestingly, only 2 genotypes we found in South Africa, were shared with other countries around the world. Because this study is centred on contributing to the development of a recombinant subunit vaccine, this strain variation should be taken into account in such an undertaking. The current A. centrale blood vaccine has some drawbacks, the two main problems being that it does not protect against heterologous challenge with field strains of A. marginale and it may contribute to transmitting other emerging diseases resulting from a contaminated blood vaccine. Outer membrane protein (OMP) preparations are known to induce immune protection in nearly all animals tested, thus demonstrating the potential efficacy of a subunit vaccine. Five potential OMP vaccine candidates Am779, Am854, Omp7, Omp8 and Omp9 were identified from North American A. marginale strains and have been well-characterised in A. marginale strains from United States of America (USA), but their levels of conservation in other countries were not known. This information would be needed to show that they could be used in a vaccine formulation for a broad application to control bovine anaplasmosis worldwide or in making specific vaccine formulations well-suited for geographic regional strains. In this study, we demonstrated the amino acid variation in these five vaccine candidate OMPs in South African A. marginale strains. We also assessed the immunogenic relationships between South African recombinant versions of these OMPs, and the extensively studied St. Maries and Florida A. marginale strains, from USA. OMPs Am854 and Am779 were found to be highly conserved, with 99–100% amino acid identity. Omp7, Omp8 and Omp9 were also found to be conserved with 79–100% identity with St. Maries and Florida strains. We also found, as has been shown previously, that the latter OMPs possess conserved N- and Cterminals, along with a pronounced, central hypervariable region. A previously identified, highly conserved T-cell epitope, FLLVDDAI/V, was also found in the conserved Nterminus of these three OMPs. Through recognition of South African recombinant OMPs by anti-A. marginale and A. centrale bovine sera from South Africa and USA, we were able to demonstrate immunological cross-reactivity between the A. centrale and A. marginale organisms. This suggests that there are significant antigenic and immunological relationships between South Africa and USA strains of A. marginale, and provides evidence for the continued use of the A. centrale blood vaccine for immunisation against A. marginale infections. Our study also provides evidence to suggest that the A. marginale OMPs are good vaccine candidates for use in a global vaccine cocktail, although further work on the best formulation and delivery methods is necessary. For the purposes of creating a biobank of A. marginale strains for downstream ‘-omic’ studies and to provide challenge material for future vaccine trials, we attempted to culture field strains of A. marginale from 17 bovine blood samples in ISE6 and IDE8 tick cell lines. Blood from three persistently infected and 12 clinically sick animals was used to attempt direct infection of tick cell lines, but yielded negative cultures after approximately 160 days in culture. We therefore attempted to initiate cultures using blood from two splenectomised calves that were infected with blood from A. marginale-carrier animals. These have yielded promising results as small colonies could be observed after about 60 days of culture, and DNA extracts of these cultures were qPCR-positive. We will continue to monitor these cultures by Giemsa staining, light microscopy and qPCR, for progression of the infection.